(untitled) (American Journal of Business Management, Economics and Banking, 2024)
Logistics systems, which have a blood vessel, play an important role in the economic development of any country. An effective logistics system ensures the supply of goods and services at affordable and affordable prices for the customers, while stimulating competition in the market by optimizing the movement of finished goods and raw materials in the domestic market. On the foreign market, it increases the country’s economic competitiveness and accelerates its integration into the global economy. It is very important to create an effective logistics system for our developing country.